The sero-prevalence and seasonality of contagious bovine pleuropneumonia in nomadic pastoral cattle herds of Niger State, Nigeria (2016)
A cross-sectional study was conducted in the three agro-ecological zones of Niger State, Nigeria between December 2012 and August 2013 to determine the prevalence, distribution and seasonality of contagious bovine pleuropneumonia in the state. A total of 765 sera were collected from cattle in 125 nomadic herds, and were tested using competitive Enzyme Linked Immunosorbent Assay. Participator)' epidemiology survey was conducted to obtained information on the seasonal occurrence of the disease. The true prevalence at the cattle-level was 16.2% (124/765; 95% Cl: 13.7, I9.0) with Kontagora Agro-zone having the highest sero-prevalence (25.3%; 95% Cl: 20.2, 30,1) amongst the zones. The herd- level true sero-prevalence was 47.2% (59/125; 95% Cl: 38.2, 56.3) with the same Kontagora Agro-zone having the highest sero-prevalence of 72.5% (95% Cl: 56.1, 85.4) among the zones. The Kontagora Agro-zone shared border with the Republic of Benin and some international stocks routes across it significantly (p<0.000000279) had higher sero-prevalence than other zones. The nomadic pastoralists’ concordance on the most season of occurrence of CBPP is early dry season (October to December) and the agreement was very strong (Kendall’s Coefficient of Concordance fP=0.87]9) and statistically significant (P<0.01). The study showed the usefulness of population-based serological survey in detecting active infection in populations which, until now, may be considered to be free of disease by experts’ opinions. The study highlighted the benefits of conducting serological and participatory epidemiology surveys simultaneously, to ascertain the infection status of animals. These findings should be considered for strengthening active surveillance and control of CBPP in Nigeria.